Expression, purification and crystallization of the ectodomain of the envelope glycoprotein E2 from Bovine viral diarrhoea virus. Issue 1 (8th January 2013) - Iourin, Oleg; Harlos, Karl; El Omari, Kamel; Lu, Weixian; Kadlec, Jan; Iqbal, Munir; Meier, Christoph; Palmer, Andrew; Jones, Ian; Thomas, Carole; Brownlie, Joe; Grimes, Jonathan M.; et al.
<x xml:space="preserve">Abstract</x> Bovine viral diarrhoea virus (BVDV) is an economically important animal pathogen which is closely related to Hepatitis C virus. Of the structural proteins, the envelope glycoprotein E2 of BVDV is the major antigen which induces neutralizing antibodies; thus, BVDV E2 is considered as an ideal target for use in subunit vaccines. Here, the expression, purification of wild‐type and mutant forms of the ectodomain of BVDV E2 and subsequent crystallization and data collection of two crystal forms grown at low and neutral pH are reported. Native and multiple‐wavelength anomalous dispersion (MAD) data sets have been collected and structure determination is in progress.